A pearl in the ear: Intracranial complications of pediatric cholesteatomas. (January 2017) - Basa, Krystyne; Levi, Jessica R.; Field, Erin; O'Reilly, Robert C.
Abstract: A nine-year-old male had a cholesteatoma of the mastoid and middle ear found incidentally after myringotomy tube placement. Associated asymptomatic sigmoid plate dehiscence with sinus invasion or thrombosis and ossicular chain destruction complicated his case. He had canal wall down tympanomastoidectomy and was followed for 4.5 years. Disease recurrence necessitated revision. Our case highlights an unusual clinical presentation, possible complications, and the aggressive quality of a benign lesion common in the pediatric population. To our knowledge, this is the first report of an asymptomatic lateral sinus obstruction secondary to an invasive cholesteatoma in this population.